THE IMPACT OF MULTIMEDIA TOOLS ON ENGLISH VOCABULARY ACQUISITION IN PRIMARY SCHOOL STUDENTS IN UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This thesis examines how multimedia tools enhance English vocabulary acquisition among primary school students in Uzbekistan. Through comparative analysis of traditional textbook-based instruction versus multimedia-enriched teaching approaches, the research employs pre-tests, post-tests, classroom observations, and teacher interviews. The results demonstrate that multimedia integration substantially improves vocabulary retention, student motivation, and classroom engagement. These findings underscore the transformative potential of educational technologies in language learning when implemented with appropriate methodological considerations.Acknowledgements